The 'red supergiant problem': the upper luminosity boundary of Type II supernova progenitors. Issue 1 (20th January 2020) - Davies, Ben; Beasor, Emma R
ABSTRACT: By comparing the properties of red supergiant (RSG) supernova (SN) progenitors to those of field RSGs, it has been claimed that there is an absence of progenitors with luminosities L above log (L/L⊙ ) > 5.2. This is in tension with the empirical upper luminosity limit of RSGs at log (L/L⊙ ) = 5.5, a result known as the 'RSG problem'. This has been interpreted as an evidence for an upper mass threshold for the formation of black holes. In this paper, we compare the observed luminosities of RSG SN progenitors with the observed RSG L -distribution in the Magellanic Clouds. Our results indicate that the absence of bright SN II-P/L progenitors in this sample can be explained at least in part by the steepness of the L -distribution and a small sample size, and that the statistical significance of the RSG problem is between 1σ and 2σ . Secondly, we model the luminosity distribution of II-P/L progenitors as a simple power law with an upper and lower cut-off, and find an upper luminosity limit of $\log (L_{\rm hi}/\mathrm{L}_\odot) = 5.20^{+0.17}_{-0.11}$ (68 per cent confidence), though this increases to ∼5.3 if one fixes the power-law slope to be that expected from theoretical arguments. Again, the results point to the significance of the RSG problem being within ∼2σ. Under the assumption that all progenitors are the result of single-star evolution, this corresponds to an upper mass limit for the parent distribution of $M_{\rm hi} = 19.2\, {\rm M_\odot }$, $\pm 1.3 \, {\rm M_\odot (systematic)}$, $^{+4.5}_{-2.3} \, {\rm M_\odot }$ (random; 68 per cent confidence limits).